The law and the prophets Old Testament studies prepared in honour of Oswald Thompson Allis - Skilton, John H.; Fisher, Milton C.; Sloat, Leslie W. (Nutley, NJ Presbyterian and Reformed, 1974)
Includes bibliographical references.
Keywords: Allis, Oswald Thompson -- 1880-1973; Bible. O.T. -- Essays, lectures, addresses